Hepatic Superscan on [18F]-FDG Positron Emission Tomography/Computed Tomography - Dhanasekar, Rajalakshmi; Hephzibah, Julie; Kodiatte, Thomas; John, Junita Rachel (World Journal of Nuclear Medicine, 2025)
Sarcoidosis is an idiopathic granulomatous disease most commonly involving the lungs; however, isolated extrapulmonary manifestations such as hepatic sarcoidosis are rare and diagnostically challenging. We describe a case of hepatic sarcoidosis in a 24-year-old man who presented with a three-month history of low-grade fever and unintentional weight loss. Clinical examination was unremarkable, and initial blood investigations revealed elevated alkaline phosphatase, lactate dehydrogenase, inflammatory markers, and serum ACE levels, with a negative work-up for tuberculosis and autoimmune diseases. Chest imaging was normal. [18F]-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) revealed diffuse hypermetabolic liver (hot liver) with reduced physiological uptake in the myocardium and kidneys, consistent with a hepatic superscan pattern. No significant pulmonary nodules or mediastinal/hilar nodal involvement was detected. In view of the hepatic superscan, a liver biopsy was suggested, which revealed hepatic sarcoidosis. The patient was diagnosed with ‘Hepatic sarcoidosis’ and responded well to corticosteroid therapy. This case highlights the importance of [18F] FDG PET/CT in guiding diagnosis in cases of unexplained systemic symptoms. The hepatic superscan appearance, typically associated with malignancy, can also be observed in rare granulomatous diseases such as sarcoidosis, reinforcing the need for histopathological confirmation. [18F] FDG PET/CT is also beneficial for a whole-body survey in detecting occult diseases and guiding further investigations, such as targeted biopsies.
Keywords: [18F]-FDG PET/CT; hepatic sarcoidosis; hepatic superscan; histopathology; infective etiology; infiltrative disorders